2018
DOI: 10.1002/jbmr.3546
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Fanconi Anemia C Gene in Mice Leads to Skeletal Anomalies and Defective Bone Mineralization and Microarchitecture

Abstract: Fanconi anemia (FA) is a rare genetic disorder associated with a progressive decline in hematopoietic stem cells leading to bone marrow failure. FA is also characterized by a variety of developmental defects including short stature and skeletal malformations. More than half of children affected with FA have radial-ray abnormalities, and many patients have early onset osteopenia/osteoporosis. Although many Fanconi anemia genes have been identified and a molecular pathway defined, the underlying mechanism leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…McGaughran et al suggested a relationship between FA and vertebral abnormalities [44]. Mazon et al reported a mouse model with an FA mutant gene that displayed skeletal anomalies such as vertebral fusion and defective bone mineralization [45]. In the present study, 53.6% of patients (15 /28) carried FA-related mutant variants and KEGG analysis indicated that this cohort was affected by FA genetic factors.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…McGaughran et al suggested a relationship between FA and vertebral abnormalities [44]. Mazon et al reported a mouse model with an FA mutant gene that displayed skeletal anomalies such as vertebral fusion and defective bone mineralization [45]. In the present study, 53.6% of patients (15 /28) carried FA-related mutant variants and KEGG analysis indicated that this cohort was affected by FA genetic factors.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, it has been demonstrated that mice with a mutant FA gene are susceptible to the teratogenic effects of ethanol. Such teratogenicity is largely due to acetaldehyde, a by-product of ethanol catabolism [45].…”
Section: Discussionmentioning
confidence: 99%
“…Further research on the effect of defective RAD51 on mesenchymal progenitor cell differentiation may reveal downstream effects not yet observed in other FA gene variants. 8 Despite the inability to assess bone marrow failure and malignancy in our patient due to his short survival, the similarities of the other physical findings in all four patients suggests a relatively consistent though expanding phenotype for this rare subgroup of FA. [2][3][4] Since only three prior RAD51-associated cases have been reported to date, it is difficult to discern which characteristics in our patient, such as the respiratory tract anomalies, can be attributed to prematurity verses the underlying condition.…”
Section: Discussionmentioning
confidence: 56%
“…Experiments involving FA gene knockouts have only assessed the three most common genes in FA ( FANCA , FANCC , and FANCG ). Further research on the effect of defective RAD51 on mesenchymal progenitor cell differentiation may reveal downstream effects not yet observed in other FA gene variants 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation